Radiation-induced impacts on mitochondrial DNA and the transgenerational genomic instability - Ryosuke Seino; Haruka Kubo; Kai Nishikubo; Hisanori Fukunaga (Environment International)
Background: Mitochondrial genomes are dynamically evolving and are shaped by somatic mutation and selection throughout the female germline. In this study, we investigated the radiation-induced impacts on mitochondrial DNA in vitro and in vivo, as well as the transgenerational inheritance. Methods: Human cervical cancer HeLa cells and telomerase-immortalized normal fibroblast BJ1-hTERT cells were exposed to X-rays at 0.5–8 Gy. Also, we exposed 8-week-old female C57BL/6N mice to a single whole-body dose of 2 Gy of X-rays and mated them with healthy males 1 day after irradiation. We extracted DNA from the irradiated cells, female mice, and the 2-week-old pups, then examined the mitochondrial DNA copy numbers (mtDNAcns) and radiation-induced damage by real-time quantitative PCR. Results: The mtDNAcn levels in cells increased and the intact copy ratios decreased 24 h after irradiation, resulting in the delayed shift of heteroplasmy. Also, the peripheral blood-derived mtDNAcn levels in irradiated females increased 1 day after irradiation and the intact copy rates decreased, supporting the results in vitro. Furthermore, whole blood-derived mtDNAcn levels decreased in 2-week-old pups born from irradiated mothers, indicating the mitochondrial genomic instability. Discussion: We found the delayed induction of mtDNA damage in human cancer and noncancerous cells after irradiation, as well as the same trend in mice. Furthermore, to our knowledge, this is first to demonstrate the hereditary effects of radiation on the regulation of mitochondrial genome. These provide novel insights into the significance of radiation protection and preventive medicine for not only pre-pregnancy females but also the next generation.